ChemInform Abstract: Enantioselective Catalysts for the Synthesis of α‐Substituted Allylboronates — An Accelerated Approach Towards Isomerically Pure Homoallylic Alcohols. Issue 22 (12th May 2016) - Brauns, Marcus; Muller, Frederic; Guelden, Daniel; Boese, Dietrich; Frey, Wolfgang; Breugst, Martin; Pietruszka, Joerg
Abstract: Enantiopure bis(allylboronates) (V) and (VIII) are synthesized using a Cu‐catalyzed SN 2′ reaction of tartrate based bisboronate (III) with Grignard reagents in the presence of the chiral phosphoramidite ligand.